Out-of-Office Model – the eight Factors and Barriers Controlling the Future of e-working: Array - Beno, Michal (Acta Universitatis Danubius. Œconomica, 2020)
Academics, researchers and managers have struggled for years to identify and describe exactly what constitutes effective e-working and to identify the ideal model of e-working. In the midst of the debate and discussion, some basic concepts seem to have been lost, because, as is evident, there are different definitions of e-working. We have developed a simple basic three-dimensional model of future trends and factors affecting e-working. Each of these three dimensions, namely Technology, Global changes and Generational and demographic changes, is within the control of the individual country, and each one can be developed through appropriate support and guidance. Effective e-working is a matter of developing the ability within each of the three dimensions and then choosing to apply the eight controlling factors and barriers in a balanced way. Our model provides a systematic way of incorporating best practices to overcome concerns and guide organizations through the process of building successful, sustainable and customized e-working programs that meet the demands of a changing workplace.